The Role Of Technology In Equitable Education: Policy Analysis And Implementation Challenges In Indonesia - Nur Asyikin; Wulan Rafelia; Ika Kurnia Sofiani (Penerbit Hellow Pustaka, 2025)
Equitable and quality education is a major foundation in nation building, but Indonesia still faces major challenges related to disparities in access and quality of education, especially in the 3T areas (frontier, outermost, underdeveloped). In this context, information and communication technology emerges as a strategic solution to bridge these disparities. This article discusses the role of technology in improving education access and efficiency through online learning, school digitalization, and data-based education planning management. In addition, government policies such as Merdeka Belajar are an important foundation in encouraging the transformation of digital education that is inclusive and adaptive to the needs of the times. However, the integration of technology in education still faces obstacles in the form of infrastructure gaps, internet access, and the low digital competence of educators. This research uses a literature study method with a hermeneutic approach to analyze relevant literature and policies. The results of the study show that the use of technology can significantly support the improvement of the quality of education if accompanied by strengthening the capacity of human resources, equitable infrastructure development, and sustainable and responsive policy implementation.